EVALUASI BNSP DALAM PENANGANAN KASUS BULLYING DI SEKOLAH - Mu’awanah, Risalatul; Yahya Ashari, M (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
Bullying cases that occur in Indonesia have become a terrible thing if there is no in-depth evaluation from the relevant parties. The aim of this research is to understand the SNP concept in content standard components, understand graduate competency standards and how to handle bullying cases that occur in the educational sphere. This type of research is a literature study with a qualitative approach. The researcher's data sources were collected from the latest scientific articles from various journals and newspapers that are credible and relevant to the research topic. Data analysis in the evaluation carried out by the author uses a logic model which describes the correlation between input, process or activity and outcome (impact). The results of this research can be concluded that the role of evaluation in the field of education is an urgent matter that must be paid attention to by teachers and educational institutions in general because it influences the quality, motivation and achievement of students as a measure of the success of the goals of a planned education system. Graduate competency standards are the minimum criteria for attitudes, knowledge and skills stated in the SNP. Content standards are SNP minimum standards which include material to achieve minimum competency at each level of education. The first alternative solution for dealing with bullying cases is through a humanistic extensional approach, empathetic education, effective classroom management and stakeholder involvement in handling cases that have already occurred.